2011
DOI: 10.1590/s1413-86702011000300016
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological survey of transmissible infectious diseases in a portuguese prison establishment

Abstract: A cross-sectional study was conducted in 151 (71.6%) of 211 male inmates of a regional Portuguese prison in order to establish the seroprevalence for viral hepatitis (HAV, HBV, HCV), human immunodeficiency virus (HIV), syphilis and herpes simplex virus (HSV-1 and HSV-2) and to analyze some psychosocial and criminal characteristics. Mean age was 34 years. Anti-HAV was positive in 69.5% (n = 105) and in 34.4% (n = 52) for anti-HCV. One (0.7%) person had HBsAg and 29 (19.2%) had laboratory markers of past HBV inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Our study showed that there were differences in lifetime (15.4-2.2%) and active syphilis (35.2-0.95%) prevalence among prisons. According to our results, syphilis infection among Brazilian prisoners (10.5%) (95% CI = 9.56-11.67) is higher than that of the incarcerated population in developed countries, including France (0.5%), 22 United States (0.6%), 23 Italy (2.1%), 24 Portugal (6.0%), 25 and the developing country México (2.0%). 26 However, it is lower than that of the developing country Ghana (16.5%).…”
Section: Discussionmentioning
confidence: 54%
“…Our study showed that there were differences in lifetime (15.4-2.2%) and active syphilis (35.2-0.95%) prevalence among prisons. According to our results, syphilis infection among Brazilian prisoners (10.5%) (95% CI = 9.56-11.67) is higher than that of the incarcerated population in developed countries, including France (0.5%), 22 United States (0.6%), 23 Italy (2.1%), 24 Portugal (6.0%), 25 and the developing country México (2.0%). 26 However, it is lower than that of the developing country Ghana (16.5%).…”
Section: Discussionmentioning
confidence: 54%
“…12 The trend observed in this study has also been observed in others, despite the prevalence being even higher, from 2.1 to 6.6%. 1316…”
Section: Discussionmentioning
confidence: 99%
“…24 The seroprevalence of HSV-2 infection observed in this study is also higher than that found in previous studies carried out with the prison population of other countries, such as the 14.5% described in Nigeria 25 and 19.9% from Portugal. 26 Additionally, the scarcity of studies with information related to HSV-2 infection in women deprived of liberty makes it difficult to understand the reality that permeates the prevalence and behaviors associated with this infection. Although potentially all women are vulnerable to HSV-2 infection, there are some groups particularly more exposed to certain conditions that make them more susceptible and, consequently, at greater risk of developing the disease.…”
Section: Discussionmentioning
confidence: 99%